Association of Sleep Lack with Blood Pressure and Kidney Functions among Young People in Erbil City - Ali Z. Omar; Ismail M. Maulood; Kareem K. Hamad; Hero N. Ali; Shayma B. Bapir; Almas M. R. Mahmud (Polytechnic)
Short sleep duration could be deemed a risk factor in occurring cardiovascular system and renal physiological malfunctions. Hence, the present study carried out from December 2018 to January 2019, intended to investigate the association between sleep lack with a circulation system and kidney functions among both genders of students (12 females plus 25 males) who have 18–23 years age and attending Salahaddin University-Erbil. The trial included a sleep lack group (sleep duration <6 h). The second group represented as a control (sleep duration >6 h). Blood pressure (BP) (systolic BP [SBP], diastolic BP [DBP], and mean arterial pressure [MAP]) and weights were estimated for both groups. Blood samples were taken to determine serum creatinine utilizing fully automatically biochemical analyzer and also glomerular filtration rate (GFR) was estimated and calculated according to the Cockcroft-Gault equation. The procured results revealed that SBP was elevated in all participants in the sleep lack group as compared to the control group, while no significant change in DBP was perceived. Furthermore, MAP was increased in all volunteers in the sleep-deprived group. The results also demonstrated that the serum creatinine was raised and concomitantly estimated GFR values were elevated in sleepdeprived group as compared to the control group. Pursuant to the receiver operating characteristic curve, serum creatinine can be a risk factor for sleep lack as well. In the light of the current study, it has been concluded that the sleep lack has a role in elevating SBP but not DBP and it was related with hypertension. Furthermore, the results indicated that serum creatinine was significantly increased in students with sleep lack.